Pembuatan Trikalsium Fosfat Berpori Menggunakan Metode Protein Foaming-Consolidation - Abdul Rasyid; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Protein foaming-consolidation method is a technique for production of porous tricalcium phosphate (TCP) using egg yolk as pore creating agent. The purpose of this research was to investigate slurry composition and sintering temperature effect on physical, chemical and mechanical properties of porous TCP and characterizing porous TCP as bones implant. This research start by mixing TCP powder,egg yolk, sago powder and Darvan 821A. The slurries were mechanical stirred at 150 rpm for 3 hours. Then, the slurries were casted in a cylindrical stainless stell mold and heated at 180°C for 1 hour. Subsequently, dried samples were demolded and burned at 600°C for 1 hour. For the final steps, samples were sintered at 1000, 1100 and 1200°C for 1 hour. The compressive strength of porous bodies obtained from this research was 2.29-23.78 MPa with 19.10-71.36% porosity and density worth at 0.899 - 2.557 g/cm3. Keyword : tricalcium phosphate, egg yolk, porosity, density, compressive strength